Validation and test–retest reliability of the risser patient satisfaction scale in Cyprus - Charalambous, Andreas (My University, 2010)
Aim To describe the translation, adaptation and validation of the Risser Patient Satisfaction Scale (RPSS) questionnaire into Greek language and discuss possibilities of its use in cancer care settings. Background The translation and cultural adaptation of a widely accepted, psychometrically tested tool is regarded as an essential component of effective human resource management or quality monitoring and improvement in the healthcare arena. Methods The original version of the English self-administered questionnaire consisting of 25 items was translated and validated using the internationally accepted and recommended methodology. The validation process included: assessment of the item internal consistency, using the alpha coefficient of Cronbach. Reproducibility (test–retest reliability) was tested by the Kappa correlation coefficient. Results The psychometric properties of the Greek version of the PSS were good. The internal consistency of the instrument was very good, Cronbach’s alpha was found to be 0.89 (P < 0.001) and Kappa coefficient for reproducibility was found to be 0.84 (95% CI: 0.83–0.85, P < 0.0001). Conclusions The translated and adapted Greek version is comparable with the original instrument in terms of validity and reliability. Implications for nursing management Managers should use validated patient satisfaction scales such as the RPSS in order to evaluate the quality of care in cancer care departments. The findings should be also compared using a bench mark on national and international levels.
Keywords: Greek language; Patient satisfaction; Patients; Validation therapy